"Copy and Fix": A New Technique of Harvesting Freehand and Horseshoe Tectonic Grafts. Issue 11 (November 2015) - Unknown
Abstract : Purpose: To describe a new technique for harvesting freehand and horseshoe tectonic corneal grafts. Methods: A retrospective, noncomparative interventional case series of 3 eyes from 2 patients was included. The area to be excised from the host was marked with a marking pen. Using the principle of the light table from architecture, the donor corneoscleral rim was placed over the marked area with an ophthalmic viscoelastic device in the interface to provide a coupling medium. The donor was then marked, tracing the exact shape of the tectonic graft with a 0.2-mm overlap ("copy"). This was harvested after mounting on an artificial anterior chamber and sutured in place with 10-0 nylon ("fix") to provide an exact copy of the eccentric or horseshoe shape of the tectonic graft. One eye had a full-thickness freehand tectonic corneal graft for perforated microbial keratitis too large to glue. Two eyes from the same patient had anterior lamellar horseshoe tectonic grafts for Terrien marginal degeneration. Results: None of the grafts required any modification in their dimensions after harvesting. All grafts were easy to perform and tectonically stable postoperatively. A significant visual improvement was observed in all cases. Conclusions: The "copy and fix" technique is a simple and effective new technique that consistently and accurately maps and harvests freehand and horseshoe tectonic corneal grafts. Abstract : Supplemental Digital Content is Available in the Text.